DEMOGRAPHIC PROFILE OF MECHANICALLY VENTILATED CRITICALLY ILL ADULT PATIENT WITH PAIN - INDAH SRI WAHYUNINGSIH (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2017)
Background: Pain is experience of critically ill adult patient with ventilator. It is various among patient from moderate to severe. Factors that may affect pain in critical patients include gender, age, severity of the disease and type of sedative use. Objective: to determine the demographics of critically ill adult patients with ventilator who experience pain. Method: This is a non-experimental quantitative study with 66 ventilated adult patient in the ICUs of the 3 hospitals in Semarang. Results: The results showed that critically aged patients with 41-60 years old pain experienced 38.3%, over 60 years of 38.8%, the almost gender is man of 66.7% with the most medical diagnoses were respiratory disorders by 45% and no use sedation is 83.3%. Conclusions: The pain experienced in adult critical patients can be seen from the demographics of patients such as age, gender, medical diagnosis and sedation use. Keywords : Pain assessment, criticall ill, adult, ventilator